The Gambia : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This Selected Issues paper and Statistical Appendix for The Gambia underlies that the exchange rate is broadly in line with fundamentals, although data weaknesses and uncertainties prevent a definitive assessment. The Gambia's current account deficit is higher than economic fundamentals would predict, and a depreciation of 11 percent would be needed to restore sustainability. The external sustainability approach suggests that 4-6 percent depreciation is needed for the current account deficit to be consistent with constant net foreign assets as a share of GDP.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet